2018
DOI: 10.1111/maec.12530
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of the collector urchin, Tripneustes gratilla, in the Indonesian archipelago

Abstract: The population genetics of the economically important collector urchin, Tripneustes gratilla, were examined in 353 individuals collected from 16 sampling sites throughout Indonesia at 12 microsatellite loci. Bayesian clustering methods over all sampling locations revealed evidence of two genetically distinct clusters, one located predominantly on the shallow Sunda Shelf and the second in the deep waters associated with the biogeographic region known as Wallacea; further analysis revealed additional genetic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 105 publications
(118 reference statements)
1
11
0
Order By: Relevance
“…The idea that habitat differences in the marine environment can drive population differentiation has been invoked to explain genetic structuring and the high diversity of coral reefs in Southeast Asia (Benzie, ; Bowen, Rocha, Toonen, Karl, & Laboratory, ; Palumbi, ; Sato et al, ; Wainwright, Arlyza, & Karl, ). Correspondingly, we suggest that differences in habitat type work in conjunction with dispersal limitations to structure fungal communities.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that habitat differences in the marine environment can drive population differentiation has been invoked to explain genetic structuring and the high diversity of coral reefs in Southeast Asia (Benzie, ; Bowen, Rocha, Toonen, Karl, & Laboratory, ; Palumbi, ; Sato et al, ; Wainwright, Arlyza, & Karl, ). Correspondingly, we suggest that differences in habitat type work in conjunction with dispersal limitations to structure fungal communities.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, connectivity may be restricted due to the relatively sheltered nature of the bay, limiting water and larval movement to outside populations. Wainwright et al (2019) proposed that the observed genetic differentiation of T. gratilla is the result of habitat loss during periods of glacial maxima and differences in physical oceanographic properties throughout Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Tripneustes gratilla is one of over 1,000 described species of sea urchins (WorRMS 2020) that is widely distributed (Toha et al 2017;Mooi 2019, 2020). The habitat ranges from Pacific to African coast of the Indian Ocean, including Indonesia (Toha et al 2012;Lawrence and Agatsuma 2013;Wainwright et al 2013;Parvez et al 2018;Wainwright et al 2019). The T. gratilla has economic and ecological value (Casilagan et al 2013;Brink et al 2019, Onomu et al 2020Nane and Paramata 2020) that warrant for use of bio-indicators of marine environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that biogeographic barriers between the Indian and Pacific Oceans could restrict gene flow and obstruct the physical movement of many tropical marine species between these ocean basins. One such biogeographic barrier is the Indonesian Sunda Shelf, which has been considered to play a role in (if not entirely responsible for) the genetic differences observed among Indo-Pacific P. monodon ( Benzie et al 2002 ; You et al 2008 ; Waqairatu et al 2012 ), as well as other Indo-Pacific marine species ( Horne et al 2008 ; Gaither et al 2009 ; Simmonds et al 2018 ; Wainwright et al 2018 ). Of note is that the influence of this biogeographic barrier on gene flow remains during times of sea level rise following last glacial maximum ( Randall 1998 ; Rocha et al 2007 ; Crandall et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%